Determinan Faktor Penggunaan QRIS pada BSI Mobile - Zalsa Ayulia Pramudita; Muh. Hasbi Ash. Shiddiq; Shadriyah Shadriyah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study purposes to analyze the influence of trust and ease of use on the adoption of QRIS through mobile banking services by customers of Bank Syariah Indonesia (BSI) in Bone Regency. The main issue addressed is the relatively low adoption of QRIS in mobile banking services, which is suspected to be influenced by user trust and perceived ease of use. This research uses a quantitative approach with a survey method by distributing questionnaires to 100 participants who are users of BSI Mobile QRIS. The data were analyzed using multiple linear regression analysis. The results show that both trust and ease of use have a positive and significant influence on the use of QRIS, both partially and simultaneously. Ease of use was found to have a more dominant effect than trust. The study concludes that increasing trust and ease of use in the application can encourage the adoption of QRIS mobile banking services. Therefore, banks should enhance digital literacy efforts and ensure system reliability and security to strengthen user trust.